Pemanfaatan Media Sosial Instagram Dalam Strategi Bisnis - N, Niha; Maulana, Siddiq; Pitaloka, Winni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This literature review comprehensively examines the utilization of Instagram as a business strategy tool for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Analysis of various studies reveals Instagram’s significant role in enhancing MSME visibility, reaching new customers, and ultimately boosting sales. Effective strategies identified include profile optimization, creation of engaging visual content, utilization of paid features like Instagram Ads, and influencer collaborations. However, challenges faced by MSMEs are also discussed, encompassing digital literacy gaps, financial and technical resource constraints, and difficulties in maintaining consistent and high-quality content. The review underscores the importance of government training, mentorship, and policy support to empower MSMEs to fully leverage Instagram’s potential. Further research directions are suggested to explore specific aspects of Instagram’s impact on MSME brand awareness, customer engagement, and loyalty, as well as comparative studies between successful and less successful MSME Instagram implementations.